Mike Meyers' CompTIA Network+ guide to managing and troubleshooting networks lab manual - Weissman, Jonathan S.; Meyers, Mike ; series editor (New York : McGraw-Hill, 2022)
"Ethernet and wireless. MAC addresses, IP addresses and ports. ipconfig and netstat. ping, traceroute and nslookup. ARP, IPv4, IPv6, ICMP, ICMPv6, TCP and UDP. DNS, DHCP, HTTP, TLS, SSH, and FTP. VLANS, VPNs, and VMs. Wireshark, firewalls, and nmap. Windows and Linux. By the end of this book, you'll have a solid knowledge, understanding, and hands-on skills with all of these networking items and much more."
Includes index.
English.
Keywords: Computer networks--Handbooks, Manuals, etc